Differences in fouling community composition and space occupation across broad spatial and temporal scales - Jewett, Elizabeth B.; Lawson, Katherine N.; Larson, Kristen J.; Tracy, Brianna M.; Altman, Safra; Chang, Andrew L.; Cowan, Scott; Crooks, Jeffrey A.; Huber, Tamar; Wells, Elizabeth H.; Ruiz, Gregory M. (Frontiers in Marine Science, 2022)
Sessile marine invertebrate (biofouling) communities have served as an important model in ecology for evaluating fundamental patterns and processes, including invasion dynamics, which vary at broad spatial and temporal scales. Here, we tested for differences in biofouling community development among three biogeographically distinct bays in North America (Chesapeake Bay, Tampa Bay, and San Francisco Bay), exploring possible explanations for differential non-native species success. In particular, we aimed to examine if San Francisco Bay (a global hotspot for non-native species richness) differed in composition and space occupation, especially since open space can facilitate colonization. Additionally, we explored how biogeography, assembly and succession dynamics over the short and long term, and space availability affect marine communities across broad spatial scales. Patterns of community assembly differed among bays, with more bare space and less secondary cover (species settling on species) in San Francisco Bay. San Francisco Bay was also distinguished by a higher percent cover of Tunicata (almost all of which are non-native and historically absent) over multiple time scales. Cirripedia recruited on bare panels in all three Bays but cover increased only in Tampa Bay, as soak time increased. Tube-dwelling Polychaeta distinguished Chesapeake Bay from Tampa Bay and San Francisco Bay. Low-salinity events temporarily restructured the communities in all three bays. Whether differences among bays reflect coastal versus bay-specific patterns remains to be tested.